Exposure of the Population of Mindanao to Combined Natural and Anthropogenic Environmental Stressors - Hernan G Pantolla; Alex C Gonzaga (Journal of Multidisciplinary Applied Natural Science, 2024)
In 2019, El Niño Southern Oscillation (ENSO) episodes in conjunction with climate change resulted in significant adverse impacts, particularly on developing nations. The year 2019 ranked among the top three warmest years since the mid-1800s. This paper aims to comprehensively analyze the El Niño period and the worsening climate trends observed in Mindanao, Philippines, during that year. The application of spatial analysis techniques revealed the existence of poverty hotspots characterized by below-average precipitation and enduring episodes of dangerous levels of heat index. The study documented instances of crop destruction and farmers' resulting problems. The application of multivariate clustering analysis revealed a significant association between urbanization and elevated mortality rates in climate-sensitive diseases. This finding suggests that the degree of urbanization has an apparent impact on regional mortality rates, ranging from modest to substantial increases. The findings underscore the necessity of implementing early warning systems and developing and implementing mitigation and adaptation methods. This is particularly crucial in sectors susceptible to adverse effects, such as agriculture and healthcare, where the immediate consequences are already observable.